2010
DOI: 10.1007/s11606-010-1465-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Workload Reduction on the Quality of Residents’ Discharge Summaries

Abstract: BACKGROUND:The completeness of hospital discharge summaries may reflect the overall quality of interprofessional communications. The effect of reducing resident workload on clinical performance is largely unknown. OBJECTIVE: We examined the impact of reducing housestaff workload on the quality of discharge summaries, an indicator of clinical performance, as compared to discharge summaries created by trainees on a team with a more typical workload. DESIGN: Patients admitted to a medicine service at a community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 18 publications
0
51
2
1
Order By: Relevance
“…Resident workload has been shown to have an influence on resident performance and patient outcomes. [14][15][16][17] Additionally, a recent study of physician handoff practices showed that larger numbers of patient care handoffs were associated with a greater number of interruptions during handoff. 18 These interruptions are associated with increased opportunity for overlooked or omitted patient information, and may explain the greater level of discordance between PGY-3 giver and receiver.…”
Section: Discussionmentioning
confidence: 99%
“…Resident workload has been shown to have an influence on resident performance and patient outcomes. [14][15][16][17] Additionally, a recent study of physician handoff practices showed that larger numbers of patient care handoffs were associated with a greater number of interruptions during handoff. 18 These interruptions are associated with increased opportunity for overlooked or omitted patient information, and may explain the greater level of discordance between PGY-3 giver and receiver.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of workload and work-burden can be associated with poorer discharge documentation quality. 26 Third, we do not attempt to assess the accuracy of the provider documentation, only the presence/ absence of specific components. It is possible that some components included within study summaries were inaccurate and may have affected patient safety because of a communication error.…”
Section: Discussionmentioning
confidence: 99%
“…19 Beyond these traditional approaches, some programs have already introduced innovative approaches to teach specific discharge components such as documentation in discharge instructions and summaries. 31,32 Second, underlying concepts of teamwork, advanced planning, patient safety, and patient communication that are embedded in high-quality discharge care should be integrated into broader themes of training for competency in systems-based practice. These efforts, in turn, should be tied to specific outcomes such as adverse events or readmissions.…”
Section: Concept 5: Discharge Documentation As a Valuable Skillmentioning
confidence: 99%